The effect of fabrication method of hierarchical 3D TiO2 nanorod spheres on photocatalytic pollutants degradation - Lee, Siew Siang (2013)
The effect of fabrication method on the properties of hierarchical 3D TiO2 nanostructures was investigated by employing and developing both hydrothermal method and calcination method to synthesize hierarchical 3D TiO2 nanorod spheres in this study. A comprehensive comparison in terms of morphologies, crystallization, specific surface areas, light absorption capabilities, and photoluminescence spectrum was conducted between 3D TiO2 nanorod spheres synthesized via hydrothermal method and that synthesized via calcination method. A better photocatalytic activity was demonstrated over the TiO2 nanorod spheres synthesized through calcination method. This was ascribed to the better crystallization and monodispersion of the hierarchical 3D TiO2 nanorod spheres resulted from the calcination method; thus rendering it with more superior characteristics such as larger specific surface area, enhanced light absorption capability and faster transfer of electrons which suppress the recombination of photogenerated electrons and holes. This study is thus significant not only in promoting the development of hierarchical 3D TiO2 nanorod spheres via different methods, but also in revealing the effect of fabrication method on the photocatalytic activity of hierarchical 3D TiO2 nanorod spheres. The calcination method is proposed to be a facile and promising method for scale-up production of the hierarchical 3D TiO2 nanorod spheres with high photocatalytic activity for efficient pollutants degradation.